Human influence on the continental Si budget during the last 4300 years: δ30Sidiatom in varved lake sediments (Tiefer See, NE Germany). (15th April 2021) - Nantke, Carla K.M.; Brauer, Achim; Frings, Patrick J.; Czymzik, Markus; Hübener, Thomas; Stadmark, Johanna; Dellwig, Olaf; Roeser, Patricia; Conley, Daniel J.
Abstract: The continental silicon (Si) cycle, including terrestrial and freshwater ecosystems (lakes, rivers, estuaries), acts as a filter and modulates the amount of Si transported to the oceans. In order to link the variation in the terrestrial Si cycle to aquatic ecosystems, knowledge on changes in vegetation cover, soil disturbance and the impact of human activity are required. This study on varved lake sediments from Tiefer See near Klocksin (TSK) in northeastern Germany investigates Si isotope variations in diatom frustules (δ 30 Sidiatom ) over the last ∼4300 years. δ 30 Sidiatom values vary between 0.37 and 1.63‰. The isotopic signal measured in centric (mostly planktonic) and pennate (mostly benthic) diatoms shows the same trend through most of the record. A decrease in δ 30 Sidiatom coinciding with early deforestation between 3900 and 750 a BP in the catchment area, points to an enhanced export of isotopically light dissolved silica (DSi) from adjacent soils to the lake. The burial flux of biogenic silica (BSi) observed in the lake sediments increases with cultivation due to enhanced nutrient supply (N, P and Si) from the watershed and nutrient redistribution caused by wind-driven increased water circulation. When the cultivation intensifies, we observe a shift to higher δ 30 Sidiatom values that we interpret to reflect a diminished Si soil pool and the preferential removal of the lighter 28 Si by crop harvesting. Human activity influences the DSi supply from the catchment and appears to be the primary driver controlling the Si budget in TSK. Our data shows how land use triggers variations in continental Si cycling on centennial timescales and provides important information on the underlying processes. Highlights: Study of Si isotopes and BSi from lake sediments during the last 4300 years. DSi fluxes are the main control on Si cycling in Tiefer See. Vegetation changes and landscape cultivation alter Si fluxes. Crop harvest reduces Si availability in the catchment.